2007
DOI: 10.1108/16605370780000160
|View full text |Cite
|
Sign up to set email alerts
|

How to promote a cross‐border region as a tourism destination – the case study of the bug Euroregion

Abstract: As much as any cross‐border destination may be an attractive notion, it clearly requires more profound research as both theoretical and practical research seems hardly satisfactory. This paper will attempt to present tourism development of the cross‐border region of Bug, consisting of three national components: Polish, Belarusian and Ukrainian. There are both advantages and disadvantages resulting from the fact that one part of the destination belongs to the European Union (EU) and the other does not. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In this context, the tourist attractiveness of transboundary protected areas is determined by two key attributes -natural resources under legal protection and the border location, which is considered a tourist asset in and of itself (Więckowski, 2010), which is further enhanced by a rich cultural heritage. As a specific form of cross-border cooperation framework, the TBR should provide an opportunity to create an attractive tourist destination by popularising it and creating a common management system (Studzieniecki & Mazurek, 2007;Vasilijević et al, 2015;Studzieniecki et al, 2020). In this way, it should provide input for sustainable regional economic development and bring benefits to local communities and other stakeholders from all countries concerned.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the tourist attractiveness of transboundary protected areas is determined by two key attributes -natural resources under legal protection and the border location, which is considered a tourist asset in and of itself (Więckowski, 2010), which is further enhanced by a rich cultural heritage. As a specific form of cross-border cooperation framework, the TBR should provide an opportunity to create an attractive tourist destination by popularising it and creating a common management system (Studzieniecki & Mazurek, 2007;Vasilijević et al, 2015;Studzieniecki et al, 2020). In this way, it should provide input for sustainable regional economic development and bring benefits to local communities and other stakeholders from all countries concerned.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of population size, the identified initiatives range from 200,000 (Euregio Silva Nortica) to 7 million (Centrope). Studzieniecki and Mazurek [34], based on their experience in Bug (between Poland, Belarus and Ukraine), concluded that moving towards establishing a tourism destination is a process that is probably overambitious. Thus, an "umbrella" approach, which is looser, could be more effective as a first step.…”
Section: Cross Border Areas Place Branding and Tourism Development: A Literature Reviewmentioning
confidence: 99%
“…Understanding supply issues: the benefits and challenges of cross-border destination marketing Cross-border destination marketing is a unique concept that is rarely practiced by countries that share border attractions, regardless of its advantages. Marketing cooperation efforts that transcend national borders are important in creating synergetic effects (Studzieniecki and Mazurek, 2007), enhancing CBR growth (Dyer et al, 2007;Hoekman et al, 2008) and multiplying tourism income (Studzieniecki and Mazurek, 2007). It is also argued that cooperation improves a region's investment prospects (Dyer et al, 2007) and thus helps to attract large numbers of tourists (Makkonen, 2016).…”
Section: Understanding Demand Issues: Travel Motivations and Satisfactionmentioning
confidence: 99%
“…This could be an important contribution for both Zambia and Zimbabwe as their economies are currently struggling. Cross-border cooperation is also beneficial in solving challenges such as long queues, bureaucratic processes and poor service quality (Studzieniecki and Mazurek, 2007). These advantages have been largely reported in the EU, where over 400 million nationals travel without the hassles of passport checks and border controls (Blasco et al, 2014), compared to countries sharing border attractions, as in the case of Zambia and Zimbabwe, as well as other destinations globally.…”
Section: Understanding Demand Issues: Travel Motivations and Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation